Przesłanki powodzenia fuzji i przejęć przedsiębiorstw - Bąk, Robert; Sierpińska, Maria (Conditions for the Success of Mergers and Acquisitions of Companies, 2008)
Mergers and acquisitions are one of the most important factors influencing dynamics of the world economy growth. At the same time large number of acquisitions turns out to be unsuccessful. That fact prompts to examine reasons for failures and factors having influence on success of M&A. In the article, an attempt to systematize researchers' and specialists-practitioners' opinions on factors that play a key role in acquisition success was made, as complexity of M&A processes causes that only actions resulting from reliable analysis, that are afterwards well planned and carried out may bring results expected by the entities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 28-38